PENERAPAN PSAK 71 DAN DAMPAKNYA TERHADAP KEWAJIBAN PENYEDIAAN MODAL MINIMUM BANK - Suroso Suroso (Jurnal Bina Akuntansi, 2017)
PSAK 71 is about Financial Instrument has been applied since January 1st 2019. But in fact the implementation of this PSAK is still in consideration. DSAK-IAI much more concern about the accuracy of the implementation of PSAK 71 especially in Financial and Banking Sector. Finally DSAK IAI decided that later in 2020 all firms should implement this regulation. Some firms are allow to implement PSAK 71 early in order to make sure the firms can learn and sincronize their report with this PSAK. This research conducted base on current situation of the Bank where researcher work. This research is qualitative study of the impact of this new PSAK 71 to the Bank where Researcher work. Finding of this research, the implementation of PSAK 71 has positive impact, it could give relevant information for the user of financial report to give valuation about total, period and uncertainty about future cash flow. But there is some negative impact such as it will increase CKPN and decrease KPPM (or Capital Adequacy Ratio). There will be about 55,68% increasing of CKPN and 0,28% decreasing of KPPM. It is very important for Bank to make good preparation from the strategic aspect, technical and operational aspect because the decreasing of CKPN could impact the Bank performance and there will be more risk to be handled for the Bank.